AN EXPLORATORY STUDY ON JOB HOPPING IN SRI LANKA: A STUDY ON GENERATION ‘Y’ EMPLOYEES - Thennakoon, T.M.N.D.; Dharmawansha, P.A.P.N. (My University, 2014)
Job Hopping is a major challenge that can be observed in the today’s labor market, with the new generation working in the modern world of work. The researcher sheds light on this matter from the employees’ and employers’ point of view, with the intention of identifying the reasons, challenges and consequences of job hopping. This study concentrates on the Sri Lankan context as the studies in the western organizational contexts regarding Job Hopping, may not be applicable to organizations in Sri Lanka, due to economic, social and cultural differences. As per the findings related to Sri Lankan context, the first five reasons for employees to job hop are, pay package, career growth, working environment and culture, reputation of the organization and job security. The researcher also found differences in the nature of job hopping with regard to gender, level of education, industries the employees are employed in, and also the uncertainty avoidance behavior of employees in Sri Lanka. However, both employees and HR managers see the pros and cons of job hopping, and accept employee behavior of job hopping.
Keywords: Job Hopping; Generation Y; Labour Turnover